Technical-economical analysis of selected decentralized technologies for municipal wastewater treatment in the city of Rome - Gavasci, Renato (Water science and technology : a journal of the International Association on Water Pollution Research, 2010)
Several wastewater treatment technologies were evaluated as alternative systems to the more traditional centralized continuous flow system to serve decentralized areas of the city of Rome (Italy). For instance, the following technologies were selected: (1) Constructed wetlands, (2) Membrane Biological Reactor, (3) Deep Shaft, (4) Sequencing Batch Reactor, and (5) Combined Filtration and UV-disinfection. Such systems were distinguished based on the limits they are potentially capable of accomplishing on the effluent. Consequently, the SBR and DS were grouped together for their capability to comply with the standards for the discharge into surface waters (according to the Italian D.Lgs. 152/06, Table 1, All. 5), whereas the MBR and tertiary system (Filtration+UVc-disinfection) were considered together as they should be able to allow effluent discharge into soil (according to the Italian D.Lgs. 152/06, Table 4, All. 5) and/or reuse (according to the Italian D.M. 185/03). Both groups of technologies were evaluated in comparison with the more common continuous flow treatment sequence consisting of a biological activated sludge tank followed by the secondary settlement, with final chlorination. CWs were studied separately as a solution for decentralized urban areas with limited population. After the analysis of the main technical features, an economical estimate was carried out taking into account the investment, operation and maintenance costs as a function of the plant's capacity. The analysis was based on real data provided by the Company who manages the entire water system of the City of Rome (Acea Ato 2 S.p.A.). A preliminary design of the treatment plants using some of the selected technologies was finally carried out